Non-neuromodulatory Optogenetic Tools in Zebrafish - Varady, Adam; Distel, Martin (Frontiers in Cell and Developmental Biology, 2020)
The zebrafish (Danio rerio) is a popular vertebrate model organism to investigate molecular mechanisms driving development and disease. Due to its transparency at embryonic and larval stages, investigations in the living organism are possible with subcellular resolution using intravital microscopy. The beneficial optical characteristics of zebrafish not only allow for passive observation, but also active manipulation of proteins and cells by light using optogenetic tools. Initially, photosensitive ion channels have been applied for neurobiological studies in zebrafish to dissect complex behaviors on a cellular level. More recently, exciting non-neural optogenetic tools have been established to control gene expression or protein localization and activity, allowing for unprecedented non-invasive and precise manipulation of various aspects of cellular physiology. Zebrafish will likely be a vertebrate model organism at the forefront of in vivo application of non-neural optogenetic tools and pioneering work has already been performed. In this review, we provide an overview of non-neuromodulatory optogenetic tools successfully applied in zebrafish to control gene expression, protein localization, cell signaling, migration and cell ablation.